Potensi Kopi Arabika MENGGALI POTENSI KOPI ARABIKA: KELAYAKAN USAHA PENGOLAHAN KOPI ARABIKA DI KECAMATAN PANGATIKAN KABUPATEN GARUT: Aspek Non Finansial, Finansial, Analisis sensitivitas, dan analisis nilai pengganti - Dadan Suryana; Ahmad Choibar Tridakusumah; Anne Charina (Politeknik Negeri Lampung., 2024)
Coffee is a leading plantation commodity in Garut Regency. This study aims to analyze business feasibility from non-financial and financial aspects, as well as to assess the level of sensitivity and substitute value analysis to fluctuations in raw material prices. The method used is descriptive quantitative, focusing on analyzing the business feasibility from non-financial and financial aspects. Non-financial aspects included market, technical, management and legal, social, economic and cultural, and environmental aspects. Financial aspects were analyzed using cash flow and investment criteria such as NPV, Gross B/C, Net B/C, IRR, and PP. In addition, sensitivity analysis and surrogate value analysis were also used. Translated with DeepL.com (free version). The results of the business feasibility analysis from non-financial aspects show that this business is feasible despite the shortcomings in the technical aspects, which can be offset by market and environmental aspects. From a financial perspective, the Talaga Hurip Arabica Coffee processing business is also declared feasible, with an inflow of Rp 52,800,000 resulting from the sale of 240 kg of coffee at a price of Rp 220,000/kg. Outflow includes investment costs of Rp 69,942,000 with depreciation of Rp 7,565,725/year, fixed costs of Rp 11,107,000/year, and variable costs of Rp 25,050,400/year. The investment feasibility criteria in this study show an NPV of IDR 24,042,745, Gross B/C of 1.09, Net B/C of 1.55, IRR of 24.65 percent, and PP of 6.1 years, which means that the Talaga Hurip Kopi business meets all investment feasibility criteria. However, the sensitivity analysis shows that if coffee prices increase by more than 10 percent, the business will not be viable. Translated with DeepL.com (free version). Keywords: Arabica Coffee, Business Feasibility, Coffee Processing